Animate prime movers: an un-exploited resource towards achieving United Nations SDG 7-future research requirements - Dastgeer, Faizan; Kalam, Akhtar; Naeem, Ayisha; Ahmad, Faraz (Bulletin of Electrical Engineering and Informatics, 2025)
Renewable energy is a prominent concept that encompasses various forms, such as solar photovoltaics, wind power, and geothermal energy. Although less familiar, animate energy resources, which include human beings and animals, may also be seen as being explored. While animal-based renewable energy generation may appear novel, different research articles, patents, and a couple of commercially available products have been developed. For the specific case of dairy farms, harnessing this resource can be coupled with appropriate exercise regimens for cows, which may lead to clean energy, animal welfare, and even potential benefits for human health. These efforts align with the sustainable development goals (SDG) of the United Nations, specifically SDG 3 and SDG 7. However, ethical concerns regarding the use of animals for energy production as well as the potential and clean nature of this resource need to be thoroughly investigated before it can be exploited on a larger scale. This research paper aims to identify deficiencies in the current relevant body of knowledge and to present requirements for future research efforts that may help tap into this resource. By exploring the potential of animate energy resources, we may contribute towards sustainable energy production while promoting animal welfare and human health.